2020
DOI: 10.1007/s00268-020-05826-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID‐19 Pandemic on Surgical Residency Training: Perspective from a Low‐Middle Income Country

Abstract: Background The COVID-19 pandemic has drastically impacted postgraduate training programmes worldwide. This study aims to evaluate the Nigerian situation with respect to surgical training, with a view to identifying gaps and proffering solutions. Methods A cross-sectional survey of surgical residents in Nigeria was conducted between 27 July 2020 and 14 August 2020. A structured questionnaire designed using the free software Google Forms ® was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 24 publications
4
21
1
Order By: Relevance
“…The American College of Surgeons and the Royal College of Surgeons of England both recommend that non-emergency procedures be delayed, except operations in cancer patients [ 15 ]. Limiting the performance of elective clinical cases protects patients from in-hospital viral transmission and makes wards and critical care beds available for possible upsurges in the numbers of SARS-CoV‑2 cases.…”
Section: Discussionmentioning
confidence: 99%
“…The American College of Surgeons and the Royal College of Surgeons of England both recommend that non-emergency procedures be delayed, except operations in cancer patients [ 15 ]. Limiting the performance of elective clinical cases protects patients from in-hospital viral transmission and makes wards and critical care beds available for possible upsurges in the numbers of SARS-CoV‑2 cases.…”
Section: Discussionmentioning
confidence: 99%
“…A great number of studies have reported a detrimental effect on surgical training. The majority of them described it ‘severe’ or ‘significant’ and some even ‘catastrophic’ [ 19 , 21 , 22 , 28 , 30 43 ]. These reports come both from developed [ 13 , 21 , 22 , 24 , 26 , 31 34 , 44 52 ] and developing countries [ 28 , 30 , 35 , 53 55 ] with very different healthcare systems.…”
Section: An Overviewmentioning
confidence: 99%
“…The majority of them described it ‘severe’ or ‘significant’ and some even ‘catastrophic’ [ 19 , 21 , 22 , 28 , 30 43 ]. These reports come both from developed [ 13 , 21 , 22 , 24 , 26 , 31 34 , 44 52 ] and developing countries [ 28 , 30 , 35 , 53 55 ] with very different healthcare systems. Moreover, the results were uniform between a variety of surgical specialties; general surgery [ 13 , 19 , 21 , 30 , 32 , 34 , 37 , 41 , 42 , 44 , 47 , 56 , 57 ], orthopaedics [ 19 , 24 , 58 ], ENT (ear, nose, throat) surgery [ 19 , 31 , 50 ], vascular surgery [ 19 , 22 , 26 ], urology [ 22 , 26 , 53 ], oral and maxillofacial surgery [ 19 , 33 ], and neurosurgery [ 19 , 54 , 59 ].…”
Section: An Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Dear editors, Among the many detrimental consequences of the COVID-19 pandemic to transplantation, the impact on the training experiences of residents/fellows has not been explored. Trainees in other specialities and medical students have expressed concerns about adequately developing their skills during the pandemic [1,2]. A few re-assignments in a 1-or 2-year transplant training program may lead to significant loss of key training experiences and the ability to meet practice-specific milestones [3].…”
mentioning
confidence: 99%